Deskripsi Kemampuan Pemecahan Masalah Bentuk Molekul Mas Al-Mustaqim - Efa Safitri; Rody Putra Sartika; Lukman Hadi (Jurnal Ilmiah Ar-Razi, 2021)
This research is motivated by the large number of students who have difficulty working on material problems in the form of molecules. This study aims to determine the problem solving skills of class X IPA MAS Al-Mustaqim students in solving material problems in the form of molecules. The research method used is descriptive with case studies. The sample of the research was 16 students of class X IPA Mas Al-Mustaqim. Problem solving ability is measured using a written test in the form of an essay. The results of the study concluded that the ability to understand problems in the molecular shape material was high, the ability to prepare students' completion plans was high, and the ability to carry out completion plans was low.